2019
DOI: 10.1002/hup.2686
|View full text |Cite
|
Sign up to set email alerts
|

Treatments used for obsessive–compulsive disorder—An international perspective

Abstract: Objective The objective of this study was to characterise international trends in the use of psychotropic medication, psychological therapies, and novel therapies used to treat obsessive–compulsive disorder (OCD). Methods Researchers in the field of OCD were invited to contribute summary statistics on the characteristics of their samples. Consistency of summary statistics across countries was evaluated. Results The study surveyed 19 expert centres from 15 countries (Argentina, Australia, Brazil, China, Germany… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…However, this hypothesis is unlikely, considering that studies from diverse countries have found similar results (fair to mediocre model fit, as well as low factor loadings for these items). More importantly, the Brazilian Portuguese version has been used in several studies since the 1990s, showing consistent results, even in the context of multinational studies (Brakoulias et al, 2017, 2019; Boedhoe et al, 2017, 2018; Fouche et al, 2017; Kong et al, 2019). Furthermore, our findings derive from a multicenter study with dozens of evaluators that assessed patients with OCD in different Brazilian regions.…”
Section: Discussionmentioning
confidence: 94%
“…However, this hypothesis is unlikely, considering that studies from diverse countries have found similar results (fair to mediocre model fit, as well as low factor loadings for these items). More importantly, the Brazilian Portuguese version has been used in several studies since the 1990s, showing consistent results, even in the context of multinational studies (Brakoulias et al, 2017, 2019; Boedhoe et al, 2017, 2018; Fouche et al, 2017; Kong et al, 2019). Furthermore, our findings derive from a multicenter study with dozens of evaluators that assessed patients with OCD in different Brazilian regions.…”
Section: Discussionmentioning
confidence: 94%
“…More precise forms of psychosurgery are still performed in very few cases but are mostly used to treat obsessivecompulsive disorder (Brakoulias et al, 2019). Nevertheless, the idea of using psychosurgery to treat schizophrenia has recently re-emerged, albeit in a far more subtle and less invasive forms.…”
Section: Psychosurgerymentioning
confidence: 99%
“…In addition, CBT provides the patient with new coping styles and problem solving skills that may be important to prevent relapse and contribute to the long-term efficacy of DBS. Whereas guidelines for CBT in OCD have suggested offering CBT after DBS, clinical practice varies widely across institutions and often depends on local possibilities and traditions [ 9 , 10 ]. A more uniform and evidence-based approach may be beneficial for patients.…”
Section: Introductionmentioning
confidence: 99%